Orbital solutions of eight close sdB binaries and constraints on the nature of the unseen companions - Geier, S.; Ostensen, R. H.; Heber, Ulrich; Kupfer, Thomas; Maxted, P. F. L.; Barlow, B. N.; Vuckovic, Maja; Tillich, A.; Mueller, S.; Edelmann, Heinz; Classen, Lew; Mcleod, A. F. (Astronomy & Astrophysics, 2014)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars (sdBs) with massive compact companions such as white dwarfs, neutron stars, or stellar-mass black holes. In a supplementary programme we obtained time-resolved spectroscopy of known hot subdwarf binary candidates. Here we present orbital solutions of eight close sdB binaries with orbital periods ranging from 0.1 d to, which allow us to derive lower limits on the masses of their companions. Additionally, a dedicated photometric follow-up campaign was conducted to obtain light curves of the reflection-effect binary HS 2043+0615. We are able to constrain the most likely nature of the companions in all cases but one, making use of information derived from photometry and spectroscopy. Four sdBs have white dwarf companions, while another three are orbited by low-mass main sequence stars of spectral type M. © 2014 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs